Investigation of the prevalence of polycystic ovary syndrome in Hamedan province in 2021 - Fatemeh Asadi; Zahra Mahdavi Fakher; Motahareh Masoomi; Salman Khazaie (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  Polycystic Ovary Syndrome (PCOS) is the most common endocrine disorder and the main cause of infertility due to lack of ovulation in women of reproductive age. There is limited information about the prevalence of PCOS in the community. This study was conducted to investigate the prevalence of PCOS in women aged 15-49 in Hamadan province. Materials & Methods: In this cross-sectional descriptive-analytical study, the census examined the files of 1262 women aged 15-49 referred to Fatemieh Women's Teaching Hospital. The diagnosis of PCOS was evaluated by taking a history and examination based on the presence of oligomenorrhea and clinical symptoms of hyperandrogenism, including hirsutism, acne, and male pattern hair loss by gynecologists and recorded in the women's medical record. Quantitative and qualitative variables were compared between two groups with and without PCOS using t-test and chi-square tests, and statistical analyses were performed using SPSS V.16 at the level of significance less than 0.05. Results: 446 women with PCOS (35.34%) were identified from the total number of patients. Of these, 194 people (43.5%) had hirsutism, 75 (16.8%) had irregular menstruation, and 177 (39.7%) had both symptoms. Menstrual irregularity, infertility rate, mean serum testosterone level, the prevalence of hyperlipidemia, mean LDL, and total serum cholesterol were significantly higher in the PCOS group (P<0.05). Conclusion: Considering the 35% prevalence of PCOS in Hamadan province and its effect on fertility and the general health of women, health officials should make plans to reduce this disorder in society.